2012
DOI: 10.3354/aei00040
|View full text |Cite
|
Sign up to set email alerts
|

An ecosystem-based approach and management framework for the integrated evaluation of bivalve aquaculture impacts

Abstract: An ecosystem-based approach to bivalve aquaculture management is a strategy for the integration of aquaculture within the wider ecosystem, including human aspects, in such a way that it promotes sustainable development, equity, and resilience of ecosystems. Given the linkage between social and ecological systems, marine regulators require an ecosystem-based decision framework that structures and integrates the relationships between these systems and facilitates communication of aquaculture-environment interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…This 'ecological carrying capacity' is defined as the level of culture that can be supported without leading to significant changes to ecological processes, species, populations or communities in the farm environment. Although it is not explicitly stated, disease risk is considered to be a factor influencing the ecological carrying capacity of a marine ecosystem [114,116]. However, ecological carrying capacity is typically calculated using ecosystem modelling techniques [115,117] in which disease epidemiology is not taken into account.…”
Section: Final Thought: An Integrated Approach To Marine Diseasementioning
confidence: 99%
“…This 'ecological carrying capacity' is defined as the level of culture that can be supported without leading to significant changes to ecological processes, species, populations or communities in the farm environment. Although it is not explicitly stated, disease risk is considered to be a factor influencing the ecological carrying capacity of a marine ecosystem [114,116]. However, ecological carrying capacity is typically calculated using ecosystem modelling techniques [115,117] in which disease epidemiology is not taken into account.…”
Section: Final Thought: An Integrated Approach To Marine Diseasementioning
confidence: 99%
“…Ecosystem-based aquaculture management requires many specific components and tools for assessing the carrying capacity (Cranford et al 2012). A bottleneck to the establishment of an operational framework is often the need to define 'unacceptable' impacts among stakeholders (Cranford et al 2012).…”
Section: Management Of Environmental Resourcesmentioning
confidence: 99%
“…Ecosystem-based aquaculture management requires many specific components and tools for assessing the carrying capacity (Cranford et al 2012). A bottleneck to the establishment of an operational framework is often the need to define 'unacceptable' impacts among stakeholders (Cranford et al 2012). Suitable performance indicators, modelling approaches and indicator selection criteria must be adapted for offshore areas to facilitate policy-makers (and business) to set environmental standards and identify best practices and technologies for aquaculture development.…”
Section: Management Of Environmental Resourcesmentioning
confidence: 99%
“…In Sanggou Bay, phosphorus (P) was found to be deficient, whereas DIN was sufficient (Sun et al 2007). Bivalve culture can release P into the environment (Carlsson et al 2012, Cranford et al 2012, and the release of P by bivalves may have induced the high abundance of picoplankton in the Sanggou Bay B-area. Indeed, a 7 d in situ enclosure experiment in Sanggou Bay demonstrated that scallop cultivation increased the PO 4 3− concentration, as well as the abundance of picoplankton, total nanoflagellates and ciliates (Lu et al 2015a,b).…”
Section: Picoplankton In the Aquaculture Areamentioning
confidence: 99%